FORMULASI SEDIAAN GEL HAND SaNITIZER DARI EKSTRAK DAUN PUCUK IDING-IDING (Stenochlaena palustris) sebagai antiseptik alami - Fahmi Rizal; Verry Andre Fabiani; Fajar Indah Puspitasari; Ristika Oktavia Asriza (LPSDI Bina Patria, 2025)
The use of local plants in the Bangka Belitung islands, such as shoots of idat (Cratoxylum glaucum), pelawan (Tristaniopsis spp) and shoots of iding-iding (Stenochlaena palustris) has been practiced by local people for a long time as medicinal plants and vegetables. The three plants are natural ingredients that have been studied and contain very high antioxidant and antibacterial compounds. Iding-iding shoots (Stenochlaena palustris) have antimicrobial uses but their use as antiseptics has not been carried out. Iding-iding shoots have been studied to contain many flavonoids, polyphenols, hydroxycinnamic acid and anthrocyanins. In this study, the formulation of hand sanitizer gel preparations from iding-iding leaf extract (Stenochlaena palustris) as a natural antiseptic with varying concentrations in inhibiting the growth of Escherichia coli and Staphylococcus aureus will be carried out in this study. So far, there has been no research using iding-iding leaf extract (Stenochlaena palustris) in hand sanitizer gel preparations. The results showed that the leaf extract of iding-iding shoots had excellent bacterial inhibition at a concentration of 5% on E.Coli and S.Aureus bacteria.